Impact of Adjuvant Chemoradiotherapy on Survival of Resected Pancreatic Adenocarcinoma Cancer: A Surveillance, Epidemiology and End Results (SEER) Analysis - Shi, Xiaomao; Peng, Jin; Jiang, Huangang; Gao, Yu; Wang, Wenbo; Zhou, Fuxiang (Frontiers in Oncology, 2021)
Background The benefit of postoperative adjuvant chemoradiotherapy (CRT) for pancreatic cancer is still controversial. We aim is to evaluate whether adjuvant chemoradiotherapy can improve the survival rate of postoperative patients with pancreatic cancer compared with adjuvant chemotherapy. Methods Patients from the Surveillance, Epidemiology, and End Results (SEER) registry database who underwent resection of pancreatic ductal carcinoma from 2004 to 2016 were identified. Multivariate COX regression was used to determine the factors related to survival rate. The selection bias was minimized by propensity matching analysis. Results This study identified 10097 patients who received adjuvant chemotherapy (CT [n=5454]) or adjuvant chemoradiotherapy (n=4643). On multivariate analysis, age, sex, tumor size, site, grade, stage, T stage and lymph node metastasis were independent risk factors for OS. The basic clinical features were well balanced after propensity matching. After propensity matching, CRT can improve the survival rate compared with CT (median OS:22 months vs 23 months [HR,0.928; 95% CI,0.881-0.977; P = 0.004]). Subgroup analysis showed that the survival benefit of adjuvant chemoradiotherapy was more significant in patients with female (HR, 0.860 ;95% CI, 0.798-0.926; P =0.005 for interaction) and T3 (HR, 0.905 ;95% CI, 0.855-0.957; P =0.04 for interaction) and lymph node positive (HR, 0.883 ;95% CI, 0.832-0.938; P =0.005 for interaction). Conclusion Adjuvant CRT was associated with improved survival compared with adjuvant CT in patients with resection of pancreatic ductal adenocarcinoma. The benefit was more significant in patients with T3 and lymph nodes positive.